Single Scattering Adjoint Monte Carlo Electron Transport in FRENSIE. (3rd May 2020) - Kersting, Luke J.; Robinson, Alex; Moll, Eli; Britt, Philip; Gross, Lewis; Henderson, Douglass
Abstract: A new single scattering adjoint transport capability was implemented in Framework for REsearch in Nuclear ScIence and Engineering (FRENSIE). The Evaluated Electron Data Library (EEDL) was used to generate new tabulated adjoint data. All adjoint data were generated using refined EEDL data and a unit-base grid policy. Verification and validation tests were performed for the adjoint electron transport in FRENSIE. Adjoint simulation results were compared with forward simulation results for a self-adjoint infinite medium problem as well as experimental results for electron low-energy backscattering coefficients. Only a refined unit-base grid policy and coupled elastic scattering were tested for adjoint tests. The adjoint transport capability shows good agreement with the forward transport capability. The adjoint atomic excitation physics were unable to model a discrete forward source. For the self-adjoint infinite medium problems, the adjoint results matched the forward results to within 2% except near the cutoff energy. For backscattering coefficients, the adjoint results matched the forward results to within 5% for all converged bins. Overall, the adjoint transport capability was in good agreement with the forward transport capability validating the adjoint transport scheme.